Analisis Strategi Penerjemahan Idiom dan Kesepadanan Makna dalam Novel A Cup of Java - Hapsari, Tantri (Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is motivated by the importance of accurate translation of Idioms in literary works to maintain the equivalence of meaning between the source language and the target language. Idioms, as language units that have non-literal meanings, often become a challenge for translators. This study aims to analyze the translation strategies of Idioms used in the novel A Cup of Java and provide the level of equivalence of the translated idioms. The research method used is descriptive qualitative, with a content analysis approach that aims to identify, classify, and interpret the translation strategies of idioms and their equivalence of meaning contained in the novel A Cup of Java. The research data are in the form of idioms in the novel A Cup of Java and their translations. The results of the study show various translation strategies of Idioms applied, including direct equivalence, paraphrase, and omission. The level of equivalence of meaning varies depending on the strategy chosen and the context of use. This study provides insight into the complexity of translating Idioms in a literary context and its implicit impact on reader understanding.